Дослідження багатошарового поселення в уроч. Гнідавська Гірка 2009 р. - Златогорський, О.Є.; Бардецький, А.Б. (Археологічні дослідження в Україні, 2010)
Summary of 2009 research of multilayer settlement on the territory of Hnidavska Hirka tract is presented. 50 objects of various periods have been studied: of Linear Pottery and Stzhyzhovska cultures, of the Early Iron Age, of the Early Slavs, of the Ancient Rus and Mediaeval periods.